Earnings of Integrated Industries - Selden, G. C. (Quarterly Journal of Economics, 1902)
Journal Article Earnings of Integrated Industries Get access G. C. Senden G. C. Senden Northwood, New Hampshire Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 16, Issue 3, May 1902, Pages 451–456, https://doi.org/10.2307/1881986 Published: 01 May 1902